Structure, agency and change: early careers of novice principals in Sweden - Stina Jerdborg (Taylor & Francis Group, 2024)
ABSTRACTThe importance of school leaders' work for the development of schools is often highlighted in the research literature. However, school leadership is enacted in a social setting influenced by political, cultural, historical, and economic factors across societal as well as national settings. In Sweden, the turnover rates of school principals are high specifically among novice principals. This empirical study aims to contribute to our understanding of turnover related to structures and principal agency in the Swedish context by exploring the early stages of school principals' careers, their work environments, and their ideas about careers and motives for action. The study is based on interviews with 14 novice principals, situated at the site of their school leader education and their workplace. The findings show a constant movement among novice principals regarding their work location, work responsibilities, and positioning within their current status, during their first years of duty as a principal. The findings reveal how structures and career agency consolidate ongoing movements, making it challenging to develop professional agency and situated concerns. The career movements of novice principals within the Swedish market-oriented school system revealed the educational sector to be positioned as a marketplace and the principal as a wear-and-tear item.